ANALISIS STRATEGI PENGEMBANGAN USAHA TAHU PADA HOME INDUSTRI TAHU DA EN BANCAH PAKU NAGARI GERAGAHAN LUBUK BASUNG - Aufa Nabila; Amsah Hendri Doni (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to find out and analyze the most appropriate and correct business development strategy for the Tahu Da En home industry so that it is able to face business competition. Analyzed using SWOT analysis with the IFAS and EFAS matrices, it is then possible to identify important factors both internally and externally, which are the strengths, weaknesses, opportunities and threats of the Tahu Da En Home Industry. The approach used by researchers in this research is a qualitative descriptive approach. Apart from using qualitative analysis, researchers also analyzed using SWOT analysis. SWOT analysis is a tool for systematically identifying various factors for designing company strategy. From the results of the analysis, an aggressive strategy can be recommended, which ensures that the company or organization is in prime and stable condition so that it is possible to continue to expand, increase growth and achieve maximum progress. This strategy was chosen because the calculation results were in quadrant I where the total strength and weakness score was 1.64, while the total opportunity and threat score was 0.4. This quadrant position is very profitable for companies because it indicates that an organization or company is strong and has opportunities.